PENGARUH KUALITAS PELAYANAN, E-SYSTEM PERPAJAKAN, DAN SOSIALISASI PERPAJAKAN TERHADAP KEPUASAN WAJIB PAJAK - Linda Alfiatus Afifah; Susanti Susanti (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2020)
Taxes are the main source of state revenue, tax revenues are collected from the people and for the benefit of the people. The Directorate General of Taxes has made various efforts to increase tax revenue through services provided to taxpayers. This study aims to analyze the effect of service quality, taxation esystem, and tax socialization on taxpayer satisfaction at the West Sidoarjo Primary Tax Service Office. This type of research is quantitative research. The sampling technique in this study was calculated based on accidental sampling technique with a sample size of 40 respondents. The results of this study indicate that simultaneously and partially service quality, taxation e-system, and tax socialization have an effect the taxpayer satisfaction at the West Sidoarjo Primary Tax Service Office.Keywords: Service Quality, Taxation E-System, Taxpayer Satisfaction, Tax Socialization